The Research-Practice Gap on Accounting in the Public Services - Ferry, Laurence. author. aut Link
XIII, 137 p. 3 illus.
Keywords: This book considers how the practical and public policy relevance of research might be increased, and academics and practitioners can better engage to define research agendas and deliver findings relevant to accounting and accountability in the public services. To do so, an international comparative analysis of the research-practice gap in public sector accounting has been undertaken. This involved academic perspectives from over twenty countries, and practitioner perspectives from leading international professional accounting bodies actively involved in the public services arena. It was found that research is valued for informing practice, but engaging at a high level of policy engagement has been primarily by a small group of experienced researchers. For other researchers the impact accomplished may not always be valued highly in the academic community relative to other, more scholarly, activities. The book therefore looks at how engagement and impact between academics and practitioners can be increased. Laurence Ferry is Professor of Accounting at Durham University Business School, UK, and a prestigious Parliamentary Academic Fellow in public accountability 2018/19. He is a well-recognised international expert in public financial management. Iris Saliterer is Professor of Public and Non-Profit Management at the Albert-Ludwigs University in Freiburg, Germany, and was Schumpeter Fellow at Harvard University, USA, in 2015/2016. Her main research interests include performance management, public sector accounting and financial management (reforms), financial and administrative resilience, and innovative forms of public service delivery. Ileana Steccolini is Professor of Accounting & Finance at Newcastle University London, UK, and the chair and founder of the IRSPM accounting and accountability special interest group. Her research develops at the interface between accounting and public administration. Basil Tucker is currently a senior lecturer in the School of Commerce, UniSA Business School, Australia. He has published extensively on the relevance of academic research, and in particular, the research-practice “gap” in management accounting.